متطلبات الملاءة لشركات التأمين في الجزائر - رويسي،هناء; بن عمارة ،نوال (جامعة الوادي University of Eloued, 2025)
تناولت دراستنا جانبا وركيزة مهمة من جوانب عمل شركات التأمين وهو موضوع الملاءة في شركات التأمين الجزائرية، إذ تعتبر القدرة على إعادة تعويض المؤمنين لهم عند تعرضهم للمخاطر ذو أهمية كبيرة وبالغة، وهدفت الدراسة الى الاحاطة بجميع جوانب الملاءة لشركات التأمين في الجزائر وتحليلها بعد صدور قانون 2013 خاصة عنصري الالتزامات التنظيمية ومستوى هامش الملاءة وقد تم التطرق في هذا المقال الى جانبين، الجانب النظري لمتطلبات الملاءة وفق ما ينص له المشرع الجزائري، أما في الجانب التطبيقي فقد تم تحليل واقع الملاءة ومدى تطبيق متطلباتها في شركات التأمين في الجزائر، متبعين بذلك المنهج الوصفي في الجانب النظري والمنهج التحليلي بالنسبة للجانب التطبيقي. وقد توصلت الدراسة إلى هشاشة نظام الملاءة في شركات التأمين الجزائرية رغم التطور الذي شهده القطاع، وعدم كفاية نظام الملاءة (1) والذي اقتصر على المتطلبات التقنية وهامش الملاءة والعمل بما يعرف بالنظام المقترح لتقدير ملاءة الشركة والسعي وراء تطبيقه وتطويره خاصة نظام الملاءة (2). كما توصي الدراسة الى ضرورة وضع نظام ملاءة مالية جديد لشركات التأمين الجزائرية، يحتوي على متطلبات كمية متناسقة ترتبط بالمخاطر التي تواجهها شركات التأمين، ومرنة تتناسب مع كل وضعية شركة تأمين على حدى Enter your abstract here Our studies dealt with aspect and an important pillar of the work of insurance companies, which is the subject of the solvency in the Algerian insurance companies, as it is considered the ability to re -compensate the believers for them when they are exposed to risks of great importance and extremely, and the study aimed to surround all aspects of the sheet of insurance companies in Algeria and analyze them after the issuance of the 2013 law, especially the elements of organizational obligations and the level of margins of the sheet. According to what the Algerian legislator states, on the applied side, the reality of the sheet and the application of its requirements in insurance companies in Algeria, following the descriptive approach in the theoretical side and the analytical approach for the applied side. The study reached the fragility of the solvency system in the Algerian insurance companies despite the development witnessed by the sector, and the insufficient of the solvency system (1), which was limited to technical requirements and the margin of sheets and work in what is known as the proposed system to estimate the company's sheet and seek to implement and develop it, especially the solvency system (2). The study also recommends the necessity of setting a new financial solvency system for Algerian insurance companies, which contains the requirements of a consistent amount related to the risks faced by insurance companies, and flexible that is appropriate to each position of an insurance company separately.
Solvency requirements for insurance companies in Algeria, the difficulty of approach and the inevitability of implementation (case study of insurance companies in Algeria for the period 2019-2023)
مقال
Keywords: هامش الملاءة.; نظام الملاءة (1); نظام الملاءة (2); متطلبات الملاءة